Emergency management of penile strangulation: a case report and review of the Chinese literature. Issue 1 (22nd December 2008) - Xu, T; Gu, M; Wang, H
Abstract : A 36-year-old Chinese man presented to the emergency department with a steel hoop entrapment on his penis for 10 h. The constricting steel hoop was 20 mm in external diameter, 18 mm in internal diameter and 15 mm wide. To cut off the steel hoop an orthopaedic fret-saw and pinchers were used to make intermittent cutting at the opposite side. The total operation time was 100 min. The patient was discharged 4 days later with a satisfactory outcome. A review of seven cases of penile strangulation reported in the Chinese database of CNKI between 1990 and 2007 showed that tetanus prophylaxis and pain control did not receive adequate attention. A positive correlation was found between the time of incarceration and the length of hospitalisation.